PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 003 SUNGAI GUNTUNG - Rosmaini Rosmaini; Damanhuri Daud; Jessi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this research because result of study IPA SD in the class V SDN 003 Sungai Guntung I s low because the use of method is not variety. Because of that, needed a action who can repair learning process and improve result of student study. One of the method is inquiry cooperate learning method. Implementation can relize in 2 cycle.Every cycle consist of 2 meeting. In the first meeting activity of student still less success. After reflection cycle 1 total of student increase from 73% to be 90% on cycle 2 not only that. Result test of student also increase from cylce 1 with average 75% go up to be 83,33% while completeness was reach so good that is from 66,66% to be 100% increase result of all study is 27,35% from result of this research can conclude that implementation of inquiry cooperate l of learning method can increase result of study IPA SD in the class V SDN 003 Sungai Guntung.Keyword : Inquiry Cooperate Learning Method, Result of Study IPA